A feasible method for the division of ecological vulnerability and its driving forces in Southern Shaanxi. (20th December 2018) - Kang, Hou; Tao, Wendong; Chang, Yue; Zhang, Yue; Xuxiang, Li; Chen, Pei
Abstract: Southern Shaanxi is located in one of the water sources of the China's South-to-North Water Diversion Project. Evaluating ecological vulnerability can effectively supervise environmental changes and master evolving driving forces so as to guide the rational use and protection of ecological environment in regional water sources. Based on meteorological data, remote sensing images and statistical data, this study established an evaluation index system for ecological vulnerability in this special area. Taking advantage of visual expression and data mining capacity of geographical information system and remote sensing, a spatial principal component analysis method was introduced to evaluate the geospatial and temporal features of ecological vulnerability. This study established a feasible method to comprehensively assess the level of ecological vulnerability, and quantitatively analyze the driving forces that affected the ecological vulnerability in study area. The results indicated high levels of ecological vulnerability grade in the urban areas and the adjacent counties. With the accelerated urbanization, the ecological vulnerability index of the three major urban areas and their surrounding areas had gradually increasing ecological vulnerability index. The proportion of III vulnerable areas was always the largest area, which also led to an increase in the instability of the ecological environment. Over time, the most important driving force for ecological vulnerability of evaluation units in different regions was socio-economic factors, and environmental topographic factors were also important secondary factors for ecological vulnerability in Southern Shaanxi. Graphical abstract: Highlights: We evaluated the EVI of a special and neglected area on the basis of SPCA method. A feasible classification method of EVI level was proposed to exclude other factors. The quantitative method for driving force of ecological vulnerability was adopted.